2015
DOI: 10.1016/j.neuroscience.2014.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant T-cell receptor ligand RTL1000 limits inflammation and decreases infarct size after experimental ischemic stroke in middle-aged mice

Abstract: We have previously demonstrated that recombinant T-cell receptor ligand 1000 (RTL1000) reduces infarct size and improves long-term functional recovery after experimental stroke in young transgenic mice expressing human leukocyte antigen DR2 (DR2-Tg). In this study, we determined the effect of RTL1000 on infarct size in 12-month old middle-aged DR2-Tg mice, and investigated its mechanism of action. Twelve months old male DR2-Tg mice underwent 60 min of intraluminal reversible middle cerebral artery occlusion (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…We hypothesize that in old mice RTL1000 treatment might induce the migration of regulatory CD8 + cells (CD8 + CD122 + IL-10 + ) into the CNS, whereas in RTL1000-treated young mice these cells are retained in the periphery. Our studies suggest that age-dependent differences in the immune response after ischemic stroke results in pMHC protection from experimental stoke through peripheral-based immune regulation in young mice and inflammatory tissue-specific protection in older mice (Dotson et al, 2014; Zhu et al, 2015b). These studies address the interaction of stroke therapy with age, one of the important factors that contribute to the likelihood of a success in clinical trials.…”
Section: Treating Stroke In Middle-aged and Old Mice With Partial Mhcmentioning
confidence: 74%
“…We hypothesize that in old mice RTL1000 treatment might induce the migration of regulatory CD8 + cells (CD8 + CD122 + IL-10 + ) into the CNS, whereas in RTL1000-treated young mice these cells are retained in the periphery. Our studies suggest that age-dependent differences in the immune response after ischemic stroke results in pMHC protection from experimental stoke through peripheral-based immune regulation in young mice and inflammatory tissue-specific protection in older mice (Dotson et al, 2014; Zhu et al, 2015b). These studies address the interaction of stroke therapy with age, one of the important factors that contribute to the likelihood of a success in clinical trials.…”
Section: Treating Stroke In Middle-aged and Old Mice With Partial Mhcmentioning
confidence: 74%
“…Our lab has previously shown that RTLs could treat both experimental autoimmune encephalomyelitis (EAE) and experimental stroke induced by transient MCAO in mice [23, 39, 37, 40, 41, 21, 42, 43]. RTL1000 is comprised of an HLA-DR2 α1β1 moiety linked to human MOG-35-55 peptide [44] and has been shown to reduce infarct size in young, middle aged and older humanized DR2 mice treated with RTL following experimental stroke [21, 45, 22, 27, 46]. RTL1000, delivered one hour after stroke onset significantly reduced neurological scores and infarct volumes in the cortex and hemisphere after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…administered very late antigen‐4 and its counterpart vascular cell adhesion molecule‐1 via monoclonal antibodies, which improved the outcome of stroke lesions by inhibiting lymphocyte invasion . Moreover, recombinant T‐cell receptor ligands and lymphocyte egress inhibitors such as fingolimoid have also been successful in murine models of stroke …”
Section: Lymphocytes Encompass Adaptive Immune‐mediated Responses Folmentioning
confidence: 99%
“…96 Moreover, recombinant T-cell receptor ligands and lymphocyte egress inhibitors such as fingolimoid have also been successful in murine models of stroke. [97][98][99] Given the heterogeneity of T-cell phenotype, over the past 10 years researchers have been trying to elucidate the T-cell-specific factors responsible for contributing to stroke pathology. Shichita et al showed that cd T cells, but not conventional CD4 + T cells, can produce IL-17 following tMCAO, which contributes to ischaemic brain injury in an IL-23-dependent manner.…”
Section: Lymphocytes Encompass Adaptive Immunemediated Responses Follmentioning
confidence: 99%